WATER RESISTANCE OF SOLIDIFIED RADIOACTIVE WASTE - Kovalchuk, V.; Kozlov, I.; Dorozh, O.; Bogdanov, N.; Meletenko, N. (Odes'kyi Politechnichnyi Universytet. Pratsi, 2020)
The results of experimental studies of leaching characteristic of liquid radioactive waste of radionuclides from cement matrices for long-term storage are considered. It is shown that leach ability is a characteristic of the chemical resistance of matrices, indicating the ability of the matrix material to prevent the spread of radionuclides localized in them into the environment. It is noted that the rate of leaching of radionuclides from cement matrices changes with the time of their contact with aqueous media. Chronometric dependences of leaching rates are presented and analysed. It is shown that they consist of two sections of different duration. The initial section, lasting up to 250 hours, is distinguished by a higher steepness with a decrease in the absolute value of the speed to 2 orders of magnitude. The subsequent section, lasting up to 2500 hours or more, is characterized by an asymptotic decrease in speed to a constant minimum value. Approximating functions of the experimental chronometric dependences of radionuclide leaching were obtained in the form of power-logarithm expressions, valid in the intervals of the duration of the experiments, with a reliability of at least 0.9. It is shown that monovalent sodium and cesium ions are most intensively subject to leaching. The absolute values of the rates of leaching of monovalent nuclides are two to three orders of magnitude higher than those of divalent ones, all other things being equal. The content of the nuclide in the composition of the compound material has a significant effect on the leaching rate. An increase in matrix temperature promotes an increase in leaching rates, which is most likely due to a positive temperature coefficient of diffusion characteristics. Irradiation of the matrices decreases the leaching rate as a result of a decrease in the porosity of the matrix body and the formation of poorly soluble hydrates. The redox values of matrix-bound solutions have no significant effect on the leaching rate.